2015
DOI: 10.18768/ijaedu.98239
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Curriculum Framework for Developing Teachers’ Personal Knowledge Management Competencies

Abstract: This paper proposes a curriculum framework in pre-service teachers training program to develop Teachers' Personal Knowledge Management competency. Supporting the sustainable development of teachers as professionals in the knowledge society is a critical issue in teacher education. Personal knowledge management (PKM) is an intertwined macro-competency that involves cognitive, metacognitive, information, social and learning competencies. If PKM skills are taught, acquired and utilized in each discipline across t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Cheong and Tsui (2010) explored the roles and values of PKM and found that both individuals and organizations improved their competencies by using PKM. Cheng et al (2015) believe that PKM supports knowledge creation. A report by Ismail et al (2011) showed that knowledge workers manage personal knowledge through the process of retrieval, understanding and analyzing, sharing and connecting.…”
Section: The Review Of Related Studiesmentioning
confidence: 99%
“…Cheong and Tsui (2010) explored the roles and values of PKM and found that both individuals and organizations improved their competencies by using PKM. Cheng et al (2015) believe that PKM supports knowledge creation. A report by Ismail et al (2011) showed that knowledge workers manage personal knowledge through the process of retrieval, understanding and analyzing, sharing and connecting.…”
Section: The Review Of Related Studiesmentioning
confidence: 99%
“…Lifelong learning, international collaboration, and communication are among them. Research reveals that learning must be collaborative as well as collective, with new paths for knowledge advancement [21][22][23]. In terms of curriculum, learning must concentrate on curriculum change, recognise what the curriculum changes are and what they signify, understand how to respond to curriculum changes, and finally develop a practice to meet the curriculum objectives [19].…”
Section: Future Curriculummentioning
confidence: 99%
“…Unlike organizations, individuals have their own method of managing knowledge. According to Cheng et al (2015), PKM is an intertwined macro-competency that involves cognitive, metacognitive, information, social and learning competencies. A study by Cheong and Tsui (2010) investigated the important of PKM at both individual and organizational levels.…”
Section: Using Knowledge Creation Toolsmentioning
confidence: 99%